Bandabulya in Turkish Cypriot Urban Culture - Iscioglu, Deniz (Milli Folklor Dergisi, 2017)
Even though it took several forms showing diverse characteristics throughout history from antique cities to modern urban areas, the culture of market place has managed to survive to this day. This study aims to provide an insight to the municipal markets in Cyprus which are also known as Bandabulya in the Cypriot Urban Culture and examine the stages these bandabulya markets went through from past to present. The study also aims to analyze the importance of bandabulyas within the urban culture in a detailed manner. Market places play a significant role in the urban culture in Cyprus. A closer look to the effect these markets exert on the urban culture shows that Bandabulyas do have both economic, and social and cultural values. Within this framework, the purpose of this study is to give an account of the effects of Bandabuliyas on urban culture and examine the stages these markets went throughout history. In this context, the study focuses on two basic questions. The first question is: What are the effects and importance of Bandabulyas in respect of Urban Culture in Cyprus? The second one is this: What are the reasons that forced Bandabulyas to change and how did this change affect the urban culture? The results of the study addressing the market places in urban areas show that Bandabulyas play an important role on urban culture in terms of social, cultural, political and economic effects. But the most important point is more than ecenomic activities, Bandabulyas were important for the social and cultural activities. In that reason, Bandabulyas are very important for the cultural heritage in a urban place.
Keywords: Bandabulya; Market Place; Urban Culture; Cypriot Urban Culture; Turkish Cypriot Market Place